Measuring Sustainable Service Quality of Malaysian Water and Sewerage Companies: A Pilot Study - Salleh, Abrari; Mohd Yusof, Sha'ri; Othman, Norazli (2017)
Objective: The aim of this paper is to evaluate the reliability and validity of the sustainable service quality or SUSSERV instrument prior it implementation to measure service quality and sustainability among the water and sewerage companies. Methodology: The random survey data from 30 questionnaires were analysed representing customers of water and sewerage service companies in Selangor, Kuala Lumpur, and Putrajaya.Results: The findings showed that SUSSERV model with six independent variables namely tangibles, reliability, responsiveness, assurance, empathy and sustainability is valid and reliable instrument.We recommend the sampling method to be used during the final research is the quota sampling and will be based on geographical factors (districts) and category of services either water or sewerage Implication: This paper is an attempt to fill the gap between service, product and process quality.SUSSERV will be suitable to overcome the lack of research in sustainability service quality particularly in the context of Malaysian water and sewerage industry.